2006
DOI: 10.1073/pnas.0511022103
|View full text |Cite
|
Sign up to set email alerts
|

Controlling the shape, orientation, and linkage of carbon nanotube features with nano affinity templates

Abstract: Directed assembly of nanoscale building blocks such as singlewalled carbon nanotubes (SWNTs) into desired architectures is a major hurdle for a broad range of basic research and technological applications (e.g., electronic devices and sensors). Here we demonstrate a parallel assembly process that allows one to simultaneously position, shape, and link SWNTs with sub-100-nm resolution. Our method is based on the observation that SWNTs are strongly attracted to COOH-terminated self-assembled monolayers (COOH-SAMs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
193
1

Year Published

2007
2007
2014
2014

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 209 publications
(200 citation statements)
references
References 47 publications
2
193
1
Order By: Relevance
“…, carbon nanotubes 12,13 and nanowires 14 . Lithographic templates can also be used to create hierarchical order: the nanostructures they organize can themselves have internal features with dimensions significantly smaller than those of the original template 15 and can serve as scaffolds for the assembly of still smaller components.…”
mentioning
confidence: 99%
“…, carbon nanotubes 12,13 and nanowires 14 . Lithographic templates can also be used to create hierarchical order: the nanostructures they organize can themselves have internal features with dimensions significantly smaller than those of the original template 15 and can serve as scaffolds for the assembly of still smaller components.…”
mentioning
confidence: 99%
“…More specifically, block copolymer composition can be controlled to self-assemble a variety of phases: lamellar, bicontinuous, gyroid and discrete micelles [5]. Thus, with appropriate choice of polymers more structured arrangements with improved percolation of CNTs at low fractions might be possible.. Template-controlled assembly of CNTs is a problem relevant not only to nanocomposites, but to other diverse application areas [6]. Self-organization of inorganic nanoparticles in copolymers have been investigated both experimentally [7] and computationally [8,9] and dispersion of stiff rods, somewhat representative of CNTs, have been investigated in fluids and phase-separating fluid mixtures [10].…”
mentioning
confidence: 99%
“…In the dip-pen nanolithography technique, AFM cantilever is inked with organic materials, which are then transferred to flat surfaces. Recently, Wang and co-workers have demonstrated that the microcontact printing and parallel dip-pen nanolithography technique allows one to pattern single-walled carbon nanotubes functionalized with COOH-terminated self-assembled monolayers (Wang et al, 2006). Another method, called fountain-pen nanolithography (FPN), has a potential to be effective large-area patterning technique, in which the modified AFM cantilever serves as a micro-pipet.…”
Section: Introductionmentioning
confidence: 99%